2017
DOI: 10.48084/etasr.1494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soorh Metakaolin on Concrete Compressive Strength and Durability

Abstract: Concrete durability is a key aspect for forecasting the expected life time of concrete structures. In this paper, the effect of compressive strength and durability of concrete containing metakaolin developed from a local natural material (Soorh of Thatta Distict of Sindh, Pakistan) is investigated. Soorh is calcined by an electric furnace at 8000C for 2 hours to produce metakaolin. One mix of ordinary concrete and five mixes of metakaolin concrete were prepared, where cement is replaced by developed metakaolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The availability of cementitious materials varies with the locality, e.g. sorah [43] is one of the promising cementitious materials locally available in Pakistan which may be tried in SCC. Thus, it may be concluded that there is always need of understanding the behavior of SCC with materials and fibers obtained from local resources.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of cementitious materials varies with the locality, e.g. sorah [43] is one of the promising cementitious materials locally available in Pakistan which may be tried in SCC. Thus, it may be concluded that there is always need of understanding the behavior of SCC with materials and fibers obtained from local resources.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to collect a large database and, therefore, all test results of mechanical properties of concrete with MK conducted based on international standards were collected for use in this study. This database was collected from 45 published studies [ 4 , 15 , 16 , 17 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and is shown in the supplementary document . In the supplementary document, Tables S1–S3 contain the information of input parameters and output for , …”
Section: Data Collectionmentioning
confidence: 99%
“…Table S3: Experimental database of FS of concrete with metakaolin. References [ 4 , 15 , 16 , 17 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…In [6], an in-depth study was presented on the use of the concrete diffusion coefficient. The durability properties of fuel ash concrete and metakaolin concrete were studied in [13] and [14] respectively. This study aims to develop a framework for the chloride diffusion in concrete, considering the loading effect using semi-probabilistic and probabilistic analysis.…”
Section: Imentioning
confidence: 99%